1966
DOI: 10.1002/art.1780090608
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent acute inflammation associated with focal apatite crystal deposition

Abstract: SYNDROME OF RECURRENT painful periarticular lesions associated with roentgenographically demonstrable calcification was recently described by Pinals and Short.' These authors suggested ( a ) that a fundamental defect in connective tissue exists in these individuals, and ( b ) that the inflammation observed was mediated by the preformed ectopic mineral phase. The purpose of this paper is to report three additional patients with a similar clinical course and to describe limited pathologic and crystallographic fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

1968
1968
1987
1987

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(32 citation statements)
references
References 6 publications
1
31
0
Order By: Relevance
“…The present report differs from these studies in two respects: first, the amount of crystals in the synovial fluid was extremely large, giving it a unique chalky white appearance, and second, indisputable evidence that the synovial fluid particles represented crystals of the apatite series was provided by the X-ray diffraction analysis. The globular concentric laminated bodies observed by phase microscopy of the synovial fluid in the present case (Figure 3b) are similar to, though tending to be somewhat smaller than, those observed in exudates proved to contain hydroxyapatite from patients with acute periarticular inflammation (9).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The present report differs from these studies in two respects: first, the amount of crystals in the synovial fluid was extremely large, giving it a unique chalky white appearance, and second, indisputable evidence that the synovial fluid particles represented crystals of the apatite series was provided by the X-ray diffraction analysis. The globular concentric laminated bodies observed by phase microscopy of the synovial fluid in the present case (Figure 3b) are similar to, though tending to be somewhat smaller than, those observed in exudates proved to contain hydroxyapatite from patients with acute periarticular inflammation (9).…”
Section: Discussionsupporting
confidence: 78%
“…Hydroxyapatite crystals have previously been identified in bursa1 and peritendinous exudates of patients with calcific tendinitis and periarthritis (9). In addition, solitary deposits of hydroxyapatite have been found in menisci from knees of 1.4% of cadavers (10).…”
Section: Discussionmentioning
confidence: 96%
“…Hydroxyapatite crystals were identified in the disc matrix we studied by TEM, and apatite deposition disease is a common occurrence in dialysis patients. Periarticular calcifications, which are known to contain apatite crystals (1, [17][18][19], are frequently observed among patients on long-term hemodialysis (1, [20][21][22]. They affect the shoulders, hips, wrists, or interphalangeal joints, and appear on radiographs as small radiodensities located in tendons, ligaments, or capsulae.…”
Section: Discussionmentioning
confidence: 99%
“…Hydroxyapatite crystals have been found recently in the synovial fluid of patients with osteoarthritis (OA) (1)(2)(3)(4)(5). It has been suggested that these crystals play a role in the onset of OA (6), in the inflammation (1,(7)(8)(9)(10)(11)(12), or in the progression of joint destruction (2,3,13,14).…”
Section: Hydroxyapatite Deposition In Osteoarthritic Articular Cartilmentioning
confidence: 99%